2017
DOI: 10.1097/rhu.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous Involvement, Diagnostic Imprecision of Serum Immunoglobulin G4 Levels, and Discordance Between Clinical and Radiological Findings in Immunoglobulin G4–Related Pachymeningitis

Abstract: Immunoglobulin G4-related disease is an increasingly recognized, idiopathic systemic disorder that might be associated with elevated serum IgG4 level and tissue infiltration by IgG4-positive plasma cells. We describe the clinical features and biopsy findings in a patient who presented with features suggestive of pachymeningitis and multiple cranial neuropathies. Meningeal biopsy and other laboratory studies established the diagnosis of IgG4-related hypertrophic pachymeningitis. Despite treatment with corticost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Three steroid-refractory HP patients treated with RTX for 4 weeks showed clinical improvements and exhibited prominent decreases in dural thickness (61). Thus, RTX has been suggested to be a second-line therapy for steroid-refractory HP, especially for IgG4-RD (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Three steroid-refractory HP patients treated with RTX for 4 weeks showed clinical improvements and exhibited prominent decreases in dural thickness (61). Thus, RTX has been suggested to be a second-line therapy for steroid-refractory HP, especially for IgG4-RD (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Three steroid-refractory HP patients treated with RTX for four weeks showed clinical improvements and exhibited prominent decreases in dural thickness [55]. Thus, RTX has been suggested to be a second-line therapy for steroid-refractory HP, especially for IgG4-RD [56][57][58][59][60].…”
Section: Treatmentmentioning
confidence: 99%
“…IgG4‐RHP seems to have a similar course to other IgG4‐RD patients. Most IgG4‐RHP respond to corticosteroids, but rapid recurrence of symptoms of HP is reported in different case series necessitating a corticosteroid‐sparing agent such as methotrexate, azathioprine, rituximab, and rarely mycophenolate mofetil 15–17 . As we considered meningeal disease was an urgent condition, all of our cases were treated with pulse corticosteroids, showing clinical improvement.…”
Section: Age At Onset/sex Symptoms Serum Igg4 At Diagnosis (Mg/dl) An...mentioning
confidence: 87%
“…13 A case-control study, suggested that CSF IgG4 quantification could be an alternative diagnostic tool with a cut off value of 2.27 mg/dL. [15][16][17] As we considered meningeal disease was an urgent condition, all of our cases were treated with pulse corticosteroids, showing clinical improvement. Four of them received rituximab, and 1 patient received azathioprine.…”
Section: Mri Dural Thickening Locationmentioning
confidence: 98%